Drug Trafficking and the Presidential Family in Venezuela: The Narco Nephews - Castro, Daniela (2016)
An explosive combination of political turmoil, a deep economic crisis and critical security situation has Venezuela on the verge of collapse. Despite the alarming situation in the country, not everyone is doing so bad, especially those close to the ruling power. Ferraris, access to private aircrafts and bodyguards are only some of the privileges that only few can get access to in this impoverished South American nation. Efrain Antonio Campo Flores, 30, and Franqui Francisco Flores de Freitas, 31 -- the nephews of the Venezuelan Presidential couple -- were found guilty of conspiring to import hundreds of kilograms of cocaine into the U.S. https://medium.com/danielacastroromero/drug-trafficking-and-the-presidential-family-in-venezuela-15e099a7fbb4#.3waxzqgz